Implementasi Kompresi File PDF Menerapkan Algoritma Interpolative Coding - Sitorus, Jeremiati (STMIK Budi Darma, 2024)
The more technology develops today, the more difficult it is to obtain information. One of them is that using a computer indirectly increases storage needs. Computers store various kinds of data and files of different sizes, such as PDF (Portal Document Format) files. Problems found in file sizes that are too large will result in the process of sending or transferring data taking longer and affecting less storage media. The solution to overcome this problem requires compression techniques for PDF files. Compression techniques are used to reduce the bit size of data, thereby speeding up the file sending process and saving the storage media used. Lossless data compression by applying the Interpolative Coding algorithm. In applying the Interpolative Coding algorithm, it can be concluded that the compression results of initially large PDF files are compressed very well and the compression results produce a Compression Ratio of 1.91, Compression Ratio of 52.1%, Redundancy of 47.9% and Space Saving of 47.9.